1995
DOI: 10.1002/j.1460-2075.1995.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Base pairing between U3 and the pre-ribosomal RNA is required for 18S rRNA synthesis.

Abstract: The nucleolus, the site of pre-ribosomal RNA (prerRNA) synthesis and processing in eukaryotic cells, contains a number of small nucleolar RNAs (snoRNAs). Yeast U3 snoRNA is required for the processing of 18S rRNA from larger precursors and contains a region complementary to the pre-rRNA. Substitution mutations in the pre-rRNA which disrupt this base pairing potential are lethal and prevent synthesis of 18S rRNA. These mutant pre-rRNAs show defects in processing which closely resemble the effects of genetic dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
174
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(178 citation statements)
references
References 37 publications
(63 reference statements)
4
174
0
Order By: Relevance
“…These components include U3 (Dundr et al, 1997) and U14 snoRNAs (Beven et al, 1996), nucleolin, and proteins associated with C/D box-containing snoRNAs, fibrillarin, and ribonucleoprotein p52 (Dundr et al, 1996(Dundr et al, , 1997. U3 and U14 are transiently associated with some 5Ј-ETS and 18S sequences of pre-rRNA (Beltrame and Tollervey, 1995;Liang and Fournier, 1995), and they have been suggested to assemble into a hypothetical multiple-snoRNP complex (Maxwell and Fournier, 1995;Ghisolfi-Nieto et al, 1996). In addition, electron-dense "terminal balls" at the leading ends of nascent pre-rRNA transcripts have been identified as the 5Ј-ETS primary processing complexes (Kass et al, 1990;Mougey et al, 1993a), which appear to contain U3 snoRNA (Kass et al, 1990), fibrillarin (Scheer and Benavente, 1990;Mougey et al, 1993b), and nucleolin (Ghisolfi-Nieto et al, 1996;Ginisty et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These components include U3 (Dundr et al, 1997) and U14 snoRNAs (Beven et al, 1996), nucleolin, and proteins associated with C/D box-containing snoRNAs, fibrillarin, and ribonucleoprotein p52 (Dundr et al, 1996(Dundr et al, , 1997. U3 and U14 are transiently associated with some 5Ј-ETS and 18S sequences of pre-rRNA (Beltrame and Tollervey, 1995;Liang and Fournier, 1995), and they have been suggested to assemble into a hypothetical multiple-snoRNP complex (Maxwell and Fournier, 1995;Ghisolfi-Nieto et al, 1996). In addition, electron-dense "terminal balls" at the leading ends of nascent pre-rRNA transcripts have been identified as the 5Ј-ETS primary processing complexes (Kass et al, 1990;Mougey et al, 1993a), which appear to contain U3 snoRNA (Kass et al, 1990), fibrillarin (Scheer and Benavente, 1990;Mougey et al, 1993b), and nucleolin (Ghisolfi-Nieto et al, 1996;Ginisty et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotic cells, synthesis and processing of ribosomal RNAs (rRNAs) and assembly of ribosomes occur in the nucleolus and follow an unusually complex pathway+ The 18S, 5+8S, and 25-28S rRNAs are synthesized as a single precursor (pre-rRNA), which contains additional sequences that are discarded during RNA maturation+ The maturation process involves extensive modification of rRNA nucleotides, most of them guided by small nucleolar RNAs (snoRNAs), followed by multiple cleavage events resulting in the formation of different processing intermediates+ The substrate for rRNA processing is a large ribonucleoprotein complex containing a multitude of ribosomal proteins and accessory nucleolar trans-acting factors that associate with the nascent pre-rRNA (reviewed by Kressler et al+, 1999;Venema & Tollervey, 1999;Lewis & Tollervey, 2000)+ rRNA processing has been most extensively studied in the yeast Saccharomyces cerevisiae and many trans-acting factors, both proteins and ribonucleoproteins, required for the process have been characterized+ These include, in addition to guide snoRNAs, the ribonucleoprotein RNase MRP, the essential snoRNAs U3, U14, snR30 and snR10, and many proteins, which either act in association with snoRNAs or function independently+ Among the latter are putative ATPdependent RNA helicases, Dim1p methylase, and endoand exoribonucleases (Kressler et al+, 1999;Venema & Tollervey, 1999)+ Despite substantial progress in identification of the trans-acting factors required for pre-rRNA processing, their precise functions remain largely unknown+ The factor best characterized to date is the U3 snoRNP+ Based on results from yeast and vertebrate systems, it appears that U3 snoRNP plays a central role in the assembly of the machinery responsible for processing of 18S rRNA and biogenesis of the 40S ribosomal subunit (Beltrame & Tollervey, 1992;Mougey et al+, 1993;Venema & Tollervey, 1999;Borovjagin & Gerbi, 2000, and references therein)+ U3 snoRNA base pairs with the 35S pre-rRNA within the 59 external transcribed spacer (ETS) and the 59 part of 18S rRNA and is required for early cleavages at the processing sites A 0 , A 1 , and A 2 (Beltrame & Tollervey, 1995;Sharma & Tollervey, 1999;Venema & Tollervey, 1999, and references therein)+ The yeast U3 snoRNP has recently been shown to contain five strongly associated structural proteins (Watkins et al+, 2000)+ However, consistent with the central role of U3 snoRNP in rRNA maturation, immunoprecipitation (IP) experiments revealed many additional proteins associating with the particle+ These include Sof1p, Mpp10p, Imp3p, Imp4p, Dhr1p, Lcp5p, and Rcl1p (Jansen et al+, 1993;Dunbar et al+, 1997;Wiederkehr et al+, 1998;Lee & Baserga, 1999;…”
Section: Introductionmentioning
confidence: 99%
“…Yeast Rnt1p was identified by sequence homology to bacterial RNase III (Abou Elela et al+, 1996)+ Rnt1p is a double-strand specific ribonuclease that is required for the synthesis of several small nucleolar RNAs (snoRNAs) from large precursors (Chanfreau et al+, 1998a(Chanfreau et al+, , 1998bQu et al+, 1999) and for 39 end maturation of the U1, U2, and U5 small nuclear RNAs (snRNAs) (Chanfreau et al+, 1997;Abou Elela & Ares, 1998;Seipelt et al+, 1999)+ The initial functions reported for yeast Rnt1p were, however, in the processing of the prerRNA (Abou Elela et al+, 1996)+ The eukaryotic 18S, 5+8S, and 25S/28S rRNAs are transcribed as a single precursor molecule that undergoes complex posttranscriptional processing to remove the external transcribed spacers (59 ETS and 39 ETS) and internal transcribed spacers (ITS1 and ITS2)+ This process involves several exonucleolytic and endonucleolytic steps Fig+ 1B) and is largely carried out in the nucleolus+ The two earliest processing events, in the 39 ETS and at site A 0 in the 59 ETS, were reported to be inhibited in a temperature-sensitive rnt1-1 strain in vivo (Abou Elela et al+, 1996)+ In addition, model 39 ETS and 59 ETS substrates comprising stem-loop structures were specifically cleaved in vitro by the recombinant GST-Rnt1p fusion protein+ This strongly suggested that Rnt1p directly cleaved these two sites+ Since RNase III in Escherichia coli also participates in pre-rRNA processing (King et al+, 1984), this result greatly influenced models for the evolutionary origins of the eukaryotic pre-rRNA processing machinery+ Cleavage at site A 0 also requires base pairing between the U3 snoRNA and the 59 ETS (Beltrame & Tollervey, 1995)+ We therefore investigated the relationship between U3 and Rnt1p+ In the course of this work we realized that a strain completely lacking Rnt1p is, in fact, able to efficiently cleave site A 0 + In contrast, cleavage in the 39 ETS is inhibited, as previously reported (Abou Elela et al+, 1996), although the sites of in vivo Rnt1p cleavage do not match the previously reported site of in vitro cleavage+…”
Section: Introductionmentioning
confidence: 99%